Оддий қамиш, (Phragmites austra- lis) фитоценозларини қайта тиклаш ва уларни халқ хўжалигида фойдаланиш - Абдуллаева, Ж.К; Сабурова, Ш.Б; Қосназаров, Қ.Қ; Косназаров, К.А; Алламуратов, М.О (SCIENCE and SOCIETY, 2020)
The authors of this article raise the problems of millet cultivation on the fallow lands of the southern coast of This article can be used for students to write term papers, graduate works, i.e. graduate works, bachelors, master's theses, as well as graduate students and doctor- al students in their research works on this topic. The Aral Sea and improve its productivity.
Keywords: The Republic of Karakalpakstan; the Aral Sea and the Aral Sea; common reeds; phytocenoses; environmental changes; restoration problems; significance; recommendations